2016
DOI: 10.1111/ene.13002
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and apathy in Parkinson's disease: insights from neuroimaging studies

Abstract: Depression, anxiety and apathy are common mood disturbances in Parkinson's disease (PD) but their pathophysiology is unclear. Advanced neuroimaging has been increasingly used to unravel neural substrates linked to these disturbances. A systematic review is provided of neuroimaging findings in depression, anxiety and apathy in PD. A PubMed, MEDLINE and EMBASE search of peer‐reviewed original research articles on these mood disturbances in PD identified 38 studies on depression, eight on anxiety and 14 on apathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 72 publications
(244 reference statements)
8
88
1
4
Order By: Relevance
“…Furthermore, the cerebellum and locus coeruleus are a part of this complex mechanism of the motor system 24 . It is of note that these areas are also directly associated with mood symptoms 25 and anxiety in PD 26 , thereby corroborating the influence of non-motor symptoms in tremors.…”
Section: Tremor and Bradykinesiasupporting
confidence: 54%
“…Furthermore, the cerebellum and locus coeruleus are a part of this complex mechanism of the motor system 24 . It is of note that these areas are also directly associated with mood symptoms 25 and anxiety in PD 26 , thereby corroborating the influence of non-motor symptoms in tremors.…”
Section: Tremor and Bradykinesiasupporting
confidence: 54%
“…Resting‐state functional MRI (RS‐fMRI) shows that PDD patients have increased spontaneous neural activity in orbitofrontal cortex, while reduced network functional connectivity of the prefrontal‐limbic system. These results suggest the abnormalities of prefrontal‐limbic network may be involved in the complex pathophysiological mechanisms in PDD patients …”
Section: Introductionmentioning
confidence: 79%
“…Depression is one of the most common mood disturbances in PD, but its pathogenesis is unclear . Studies using advanced neuroimaging generally suggest increased neural activity in the prefrontal regions and decreased functional connectivity between the prefrontal‐limbic networks in depressed PD patients . Most of these studies have adopted position emission tomography, single‐photon emission computed tomography, structural MR, or RS‐fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies have also demonstrated widespread reduced functional connectivity in the basal ganglia network in PD patients compared with HCs . Moreover, functional neuroimaging studies have also detected that increased or decreased neural activities of the striatum in PD patients were related to mood disturbances, such as depression, apathy and anxiety . Considerable evidence has shown that the basal ganglia dysfunction may also give rise to aberrant cognition .…”
Section: Discussionmentioning
confidence: 99%